(untitled) (Journal of Atomic and Molecular Sciences, 2015)
Photoassociation reaction is the process in which two colliding atoms (or the colliding atom-molecule system) absorb a photon to form an excited molecule. Since the researches based on the ultracold atomic and molecular systems have attracted great attention both from theorists and experimentalists, the ultracold photoassociation reaction is becoming an ascendant research field. In this paper, we review briefly the investigation history of the photoassociation reaction for ultracold atoms, especially the basic theory of collision and the photoassociation in different light fields, and the research on the external-field manipulation of ultracold atoms collisions is also prospected.